Characterization of the medicinal flora used by the inhabitants of the Province of Pacasmayo, La Libertad, Peru - Gonzales Velásquez, Carmen Lizbeth Yurac (2023)
Throughout history, humans have turned to nature to obtain resources such as food, clothing, pharmaceuticals, wood and dyes. In that sense, herbalism becomes vital in improving the quality of life; Hence, the WHO states that, in countries with peripheral economies, two thirds of the population use traditional medicine as a complement to scientific medicine, which makes it a viable alternative for the population in general. For this reason, the present investigation seeks to characterize the medicinal flora used by the inhabitants of the province of Pacasmayo, La Libertad, Peru. A total of 96 semi-structured interviews were applied, which allowed collecting information concerning the taxonomy and ethnobotany of the flora used for medicinal purposes by the inhabitants of this province. It is concluded that there are 24 species of medicinal plants used in the province of Pacasmayo; distributed in 24 genera and 20 families; where Cymbopogon citratus “lemon verbena”, Rosmarinus officinalis “rosemary” and Matricaria chamomilla “chamomile” turned out to be the most important for the population